Welding rod matched with steel for high water head of pumped storage power station and production method of welding rod

By matching welding rods with steel for high heads of pumped storage power plants, using specific coating composition and chemical composition of welding cores, the problem of existing welding materials prone to defects under harsh conditions is solved, and the weld performance with high strength and low temperature impact toughness is achieved.

CN119794652APending Publication Date: 2025-04-11SHANGHAI ATLANTIC WELDING CONSUMABLES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411934858.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The high-performance welding materials built in existing large-parameter hydropower projects are prone to defects in the welds under relatively harsh service conditions, which affects the service life of the equipment.

Method used

It provides a steel supporting steel for high-head steel for pumped storage power stations, including welding cores and pill skins. The composition of pill skins is mainly calcite, calcined fluorite, calcined natural rutile, etc., and through specific chemical compositions and proportions, an efficient welding material is formed.

Benefits of technology

It realizes the high strength, low-temperature impact toughness and excellent mechanical properties of the weld, meeting the weld performance requirements of 1000MPa high-strength steel of the high-head pumped storage power station.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of welding rod preparation, and discloses a steel matched welding rod for a high water head of a pumped storage power station and a production method of the steel matched welding rod. The coating is prepared from the following components in parts by weight: 25.0 to 36.0 parts of calcite, 26.0 to 35.0 parts of calcined fluorite, 3.0 to 6.7 parts of calcined natural rutile, 3.0 to 7.0 parts of quartz sand, 2.5 to 4.0 parts of spray silicon iron, 5.5 to 7.6 parts of nickel powder, 0.5 to 0.8 part of sodium carbonate, 0.3 to 0.6 part of CMC (Carboxymethyl Cellulose), 0.6 to 1.0 part of sodium alginate, 5.0 to 6.3 parts of low-carbon ferromanganese, 9.0 to 11.0 parts of atomized iron powder, 1.8 to 2.6 parts of ferrotitanium, 0.6 to 1.0 part of rare earth fluoride and 0.6 to 1.0 part of zirconium dioxide; the production method comprises the following steps: uniformly mixing the raw materials of the coating according to the ratio, adding the adhesive into the mixture, and uniformly mixing; and the mixture and the core wire are added into a plodder, the coating is prepared on the surface of the core wire, then low-temperature baking and high-temperature baking are conducted, and the welding rod is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of welding rod preparation, and more specifically to a steel matching welding rod for high water head of a pumped storage power station and a production method thereof. Background Art

[0002] Conventional energy resources are mainly coal and hydropower, and hydropower resources are second only to coal and occupy a very important position. Hydropower construction has achieved remarkable results, but there are still many problems waiting to be solved by hydropower technicians. Among them, there are still many problems in the key manufacturing technologies of important components of large hydropower units such as turbines, volutes, steel bifurcated pipes, etc., especially the supporting welding materials. With the large-scale and large-parameter development of hydropower construction, the research and construction development of 700-100 kg super-large hydropower units, 700-800MW super-large evaporative cooling hydropower units, 100-200MW axial flow turbine generator units, and 300MW and above pumped storage units have been carried out. The steel used is mainly high-strength, high-ductility, and ultra-low welding crack special steel plates (such as CF60 (62), B610CF, CF80, etc.) suitable for large hydropower stations, pumped storage power stations and other hydropower projects.

[0003] Welding materials are indispensable materials in the equipment manufacturing process, especially the high-strength steel in hydropower station equipment. The welding materials used and the strength of the welds directly affect the overall performance of the equipment. The existing high-performance welding materials for large-parameter hydropower engineering construction still have the disadvantages of low strength, low toughness, easy corrosion, easy wear, etc. Under harsh service conditions, the welds are prone to defects, affecting the service life of the equipment. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, the present invention provides a welding rod for high-head steel in a pumped-storage power station and a production method thereof, which has the advantage of more precise operation.

[0005] To achieve the above object, the present invention provides the following technical solution: a welding rod for high-head steel of a pumped storage power station, comprising a welding core and a coating, wherein the coating is coated on the surface of the welding core;

[0006] The coating components are calculated by weight as follows: calcite: 25.0-36.0 parts, calcined fluorite: 26.0-35.0 parts, calcined natural rutile: 3.0-6.7 parts, quartz sand: 3.0-7.0 parts, sprayed ferrosilicon: 2.5-4.0 parts, nickel powder: 5.5-7.6 parts, soda ash: 0.5-0.8 parts, CMC: 0.3-0.6 parts, sodium alginate: 0.6-1.0 parts, low-carbon ferromanganese: 5.0-6.3 parts, atomized iron powder: 9.0-11.0 parts, ferrotitanium: 1.8-2.6 parts, rare earth fluoride: 0.6-1.0 parts, and zirconium dioxide: 0.6-1.0 parts.

[0007] As a preferred technical solution of the present invention, the chemical composition of the welding core is calculated by mass fraction as follows:

[0008] C:≤0.10%, Mn:0.30-0.55%, Si:≤0.08%, S:≤0.015%, P:≤0.005%, Cr:1.2~1.4%, Mo:0.8~1.0%, Ni:≤0.30%, Al:≤0.03%, Cu:≤0.20%, As:≤0.02%, and the balance is Fe.

[0009] As a preferred technical solution of the present invention, the coating components are calculated by weight as follows: calcite: 27.8 parts, calcined fluorite: 30.0 parts, calcined natural rutile: 6.7 parts, quartz sand: 5.5 parts, sprayed ferrosilicon: 3.3 parts, nickel powder: 6.5 parts, soda ash: 0.5 parts, CMC: 0.6 parts, sodium alginate: 0.8 parts, low-carbon ferromanganese: 5.2 parts, atomized iron powder: 9.0 parts, ferrotitanium: 1.8 parts, rare earth oxide: 0.9 parts, rare earth fluoride: 0.6 parts, and zirconium dioxide: 0.8 parts.

[0010] As a preferred technical solution of the present invention, the coating components are calculated by weight: 35.0 parts of calcite, 28.5 parts of calcined fluorite, 3.0 parts of calcined natural rutile, 3.0 parts of quartz sand, 3.0 parts of sprayed ferrosilicon, 6.3 parts of nickel powder, 0.7 parts of soda ash, 0.6 parts of CMC, 0.6 parts of sodium alginate, 5.9 parts of low-carbon ferromanganese, 9.0 parts of atomized iron powder, 2.0 parts of ferrotitanium, 0.8 parts of rare earth oxide, 1.0 parts of rare earth fluoride, and 0.6 parts of zirconium dioxide.

[0011] As a preferred technical solution of the present invention, the coating components are calculated by weight as follows: calcite: 26.9 parts, calcined fluorite: 33.0 parts, calcined natural rutile: 4.0 parts, quartz sand: 4.0 parts, sprayed ferrosilicon: 2.5 parts, nickel powder: 5.5 parts, soda ash: 0.8 parts, CMC: 0.3 parts, sodium alginate: 1.0 parts, low-carbon ferromanganese: 5.0 parts, atomized iron powder: 11.0 parts, ferrotitanium: 2.6 parts, rare earth oxide: 1.6 parts, rare earth fluoride: 0.8 parts, and zirconium dioxide: 1.0 parts.

[0012] As a preferred technical solution of the present invention, the mass ratio of the coating to the welding core is 3:6.5-7.5.

[0013] As a preferred technical solution of the present invention, the present invention also discloses a method for producing a welding rod for high-head steel of a pumped storage power station, comprising the following steps:

[0014] Step 1, mixing the components of the coating evenly according to the proportion, adding an adhesive to the mixture, and mixing evenly;

[0015] Step 2: Add the mixture prepared in the above step 1 and the welding core into a battening machine, prepare a coating on the surface of the welding core, and then bake it at low temperature and high temperature to obtain the welding rod.

[0016] As a preferred technical solution of the present invention, in the step 1, the weight ratio of the adhesive to the mixture is 0.2 to 0.23:1.

[0017] As a preferred technical solution of the present invention, in the step 2, the temperature of the low-temperature baking is 85°C to 110°C, and the temperature of the high-temperature baking is 380°C.

[0018] As a preferred technical solution of the present invention, the adhesive is potassium sodium water glass, and its modulus ratio is 1:0.9-1.1.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: the welding rod prepared by the present invention is used to weld high-strength steel B950CF, and the weld metal has reasonable tensile strength of 950-1130Mpa, yield strength ≥890Mpa, elongation ≥14%, -40℃ impact energy KV2 ≥47J and other mechanical performance indicators, and the weld porosity, slag inclusions, cracks, diffusible hydrogen and appearance edges after welding fully meet the requirements of 1000MPa high-strength steel for weld performance of high-head pumped storage power stations. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0021] Example 1: The components of the coating are calculated in parts by weight: calcite: 27.8 parts, calcined fluorite: 30.0 parts, calcined natural rutile: 6.7 parts, quartz sand: 5.5 parts, sprayed ferrosilicon: 3.3 parts, nickel powder: 6.5 parts, soda ash: 0.5 parts, CMC: 0.6 parts, sodium alginate: 0.8 parts, low-carbon ferromanganese: 5.2 parts, atomized iron powder: 9.0 parts, ferrotitanium: 1.8 parts, rare earth oxide: 0.9 parts, rare earth fluoride: 0.6 parts, zirconium dioxide: 0.8 parts.

[0022] The welding core uses a special welding core with low content of sulfur, phosphorus, arsenic, aluminum, etc. The chemical composition mass percentage is: C: ≤0.10%, Mn: 0.30-0.55%, Si: ≤0.08%, S: ≤0.015%, P: ≤0.005%, Cr: 1.2~1.4%, Mo: 0.8~1.0%, Ni: ≤0.30%, Al: ≤0.03%, Cu: ≤0.20%, As: ≤0.02%, Sn: ≤0.02%; the balance is Fe.

[0023] After the various components of the coating are evenly mixed, a binder is added in an amount of 23% of the weight of the coating and stirred evenly to prepare a coating paste, which is then sent to a plodder to be wrapped around the welding core, and then subjected to low-temperature baking at 110°C and high-temperature baking at 380°C to form the welding rod product of the present invention.

[0024] The welding rod produced according to the above process has stable arc, less spatter, good slag removal, good operability in all positions, beautiful weld formation, extremely low content of impurities such as S, P, As, Sb, excellent low-temperature impact toughness, low diffusible hydrogen content, excellent crack resistance, and the mechanical properties of the deposited metal are: Rm=988MPa, Rp0.2=912MPa, A=16%, (-40℃) KV2=79J, and moderate strength and plasticity.

[0025] Example 2

[0026] The components of the coating are calculated by weight as follows: calcite: 35.0 parts, calcined fluorite: 28.5 parts, calcined natural rutile: 3.0 parts, quartz sand: 3.0 parts, sprayed ferrosilicon: 3.0 parts, nickel powder: 6.3 parts, soda ash: 0.7 parts, CMC: 0.6 parts, sodium alginate: 0.6 parts, low-carbon ferromanganese: 5.9 parts, atomized iron powder: 9.0 parts, ferrotitanium: 2.0 parts, rare earth oxide: 0.8 parts, rare earth fluoride: 1.0 parts, zirconium dioxide: 0.6 parts.

[0027] The welding core uses a special welding core with low content of sulfur, phosphorus, arsenic, aluminum, etc. The chemical composition mass percentage is: C: ≤0.10%, Mn: 0.30-0.55%, Si: ≤0.08%, S: ≤0.015%, P: ≤0.005%, Cr: 1.2~1.4%, Mo: 0.8~1.0%, Ni: ≤0.30%, Al: ≤0.03%, Cu: ≤0.20%, As: ≤0.02%, Sn: ≤0.02%; the balance is Fe.

[0028] After the various components of the coating are mixed evenly, a binder is added in an amount of 20% of the weight of the coating and stirred evenly to prepare a coating paste, which is then sent to a battening machine to be wrapped on the welding core, and then baked at 85°C and 380°C to form the welding rod product of the present invention.

[0029] The welding rod produced according to the above process has stable arc, less spatter, good slag removal, good operability in all positions, beautiful weld formation, extremely low S and P impurity content, excellent low-temperature impact toughness, low diffusible hydrogen content, excellent crack resistance, and the mechanical properties of the deposited metal are: Rm=1020MPa, Rp0.2=931MPa, A=16%, (-40℃) KV2=65J, with moderate strength and plasticity.

[0030] Example 3

[0031] The components of the coating are calculated by weight as follows: calcite: 26.9 parts, calcined fluorite: 33.0 parts, calcined natural rutile: 4.0 parts, quartz sand: 4.0 parts, sprayed ferrosilicon: 2.5 parts, nickel powder: 5.5 parts, soda ash: 0.8 parts, CMC: 0.3 parts, sodium alginate: 1.0 parts, low-carbon ferromanganese: 5.0 parts, atomized iron powder: 11.0 parts, ferrotitanium: 2.6 parts, rare earth oxide: 1.6 parts, rare earth fluoride: 0.8 parts, zirconium dioxide: 1.0 parts.

[0032] The welding core uses a special welding core with low content of sulfur, phosphorus, arsenic, aluminum, etc. The chemical composition mass percentage is: C: ≤0.10%, Mn: 0.30-0.55%, Si: ≤0.08%, S: ≤0.015%, P: ≤0.005%, Cr: 1.2~1.4%, Mo: 0.8~1.0%, Ni: ≤0.30%, Al: ≤0.03%, Cu: ≤0.20%, As: ≤0.02%, Sn: ≤0.02%; the balance is Fe.

[0033] After the various components of the coating are mixed evenly, a binder is added in an amount of 20 to 23% of the weight of the coating and stirred evenly to prepare a coating paste, which is then sent to a plodder to be wrapped on the welding core, and then subjected to low-temperature baking at 100°C and high-temperature baking at 380°C to form the welding rod product of the present invention.

[0034] The welding rod produced according to the above process has stable arc, less spatter, good slag removal, good operability in all positions, beautiful weld formation, extremely low S and P impurity content, excellent low-temperature impact toughness, low diffusible hydrogen content, excellent crack resistance, and the mechanical properties of the deposited metal are: Rm=975MPa, Rp0.2=921MPa, A=17%, (-40℃) KV2=76J, with moderate strength and plasticity.

[0035] Among the components of the coating of the present invention, CaCO3 is the main component of calcite. The calcite used in the welding rod decomposes into CaO and CO2 gas under the action of arc heat, which plays the role of slag and gasification. CaO is an alkaline oxide, which can increase the basicity of slag, stabilize the arc, increase the interfacial tension and surface tension between slag and metal surface, improve the slag removal performance, and has a good S removal ability. CO2 can reduce the hydrogen partial pressure in the arc atmosphere and reduce the hydrogen content of the weld. However, too much CaCO3 (more than 36.0%) will coarsen the molten droplets, and too little CaCO3 will not produce enough CaO and CO2 gas, which cannot form slag and gas well, affecting the performance of the weld. In the present invention, the calcite is controlled at 25.0% to 36.0%.

[0036] CaF2 is the main component of calcined fluorite. It is a multi-genetic mineral and an alkaline fluoride. It is a slag-making agent, diluent and dehydrogenating agent in welding rods. CaF2 ionizes F- under the action of welding arc, which can reduce the partial pressure of hydrogen in the arc atmosphere and has the same effect as carbonate. Calcined fluorite can effectively remove the crystal water in the powder. The decomposition of CaF2 can reduce the oxygen content in the deposited metal, which is beneficial to improve the low-temperature impact toughness of the weld metal. CaF2 has a low melting point and can effectively reduce the high-temperature viscosity of the slag, improve the fluidity of the slag, and improve the conductivity and weld formation. It has a great effect on improving the welding process and improving the mechanical properties of the deposited metal. Reasonable CaF2 content can stabilize the arc. If CaF2 is too high, the arc stability will deteriorate and the slag will harden. The welding performance is better when the CaF2 content is controlled between 26.0% and 35.0%.

[0037] Calcined rutile is a purer titanium dioxide. TiO2 is an acidic oxide that can improve the physical properties of the slag, change long slag into short slag, make the slag change faster with temperature, make the weld well formed, and improve slag removal. When added, the total amount is controlled at 3.0% to 6.7%.

[0038] The addition of Ni is beneficial to improving the impact toughness of the weld. The influence of Ni on strength is much smaller than that of Mn. The effective strengthening of Ni is also much smaller than that of Mo or Cr. Moreover, Ni is harmful to the toughness of high-Mn welds. In the present invention, Ni is controlled at 5.5% to 7.6%.

[0039] Mn and Si are added as deoxidizers. In addition to the deoxidation effect, the weld strength increases with the increase of Mn, and the impact absorption work after strain aging treatment is higher. For every 0.1% increase in Mn, the yield strength and tensile strength of the weld increase by about 10MPa. When 1.5% Mn is contained, the impact toughness of the weld in the welded state and the stress relief state is the best. The deoxidation capacity of Si is 3.8 to 4.0 times that of Mn. When Si and Cr exist at the same time, the high-temperature oxidation resistance of the alloy can be improved, but too high Si is not conducive to the toughness of the weld metal. In the present invention, Si-Fe is controlled at 2.5% to 4.0%, and electrolytic manganese is controlled at 5.0% to 6.3%.

[0040] Rare earth alloy and zirconium dioxide are added to refine grains. Appropriate amounts of rare earth alloy and zirconium dioxide can improve metal structure, refine grains, increase the amount of acicular ferrite, reduce MA group members, change the form, size and distribution of inclusions, and greatly improve the low-temperature impact toughness of weld metal. In the present invention, rare earth oxide is controlled at 0.8% to 1.6%, rare earth fluoride is controlled at 0.6% to 1.0%, and zirconium dioxide is controlled at 0.6% to 1.0%.

[0041] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0042] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A welding rod for high head steel of a pumped storage power station, characterized in that: It comprises a welding core and a coating, wherein the coating is coated on the surface of the welding core; The coating components are calculated by weight as follows: calcite: 25.0-36.0 parts, calcined fluorite: 26.0-35.0 parts, calcined natural rutile: 3.0-6.7 parts, quartz sand: 3.0-7.0 parts, sprayed ferrosilicon: 2.5-4.0 parts, nickel powder: 5.5-7.6 parts, soda ash: 0.5-0.8 parts, CMC: 0.3-0.6 parts, sodium alginate: 0.6-1.0 parts, low-carbon ferromanganese: 5.0-6.3 parts, atomized iron powder: 9.0-11.0 parts, ferrotitanium: 1.8-2.6 parts, rare earth fluoride: 0.6-1.0 parts, and zirconium dioxide: 0.6-1.0 parts.

2. A welding rod for high head steel of a pumped storage power station according to claim 1, characterized in that: The chemical composition of the welding core is calculated by mass fraction: C:≤0.10%, Mn:0.30-0.55%, Si:≤0.08%, S:≤0.015%, P:≤0.005%, Cr:1.2~1.4%, Mo:0.8~1.0%, Ni:≤0.30%, Al:≤0.03%, Cu:≤0.20%, As:≤0.02%, and the balance is Fe.

3. A welding rod for high head steel of a pumped storage power station according to claim 1, characterized in that: The coating components are calculated by weight: Calcite: 27.8 parts, calcined fluorite: 30.0 parts, calcined natural rutile: 6.7 parts, quartz sand: 5.5 parts, sprayed ferrosilicon: 3.3 parts, nickel powder: 6.5 parts, soda ash: 0.5 parts, CMC: 0.6 parts, sodium alginate: 0.8 parts, low-carbon ferromanganese: 5.2 parts, atomized iron powder: 9.0 parts, ferrotitanium: 1.8 parts, rare earth oxide: 0.9 parts, rare earth fluoride: 0.6 parts, zirconium dioxide: 0.8 parts.

4. A welding rod for high-head steel of a pumped storage power station according to claim 1, characterized in that: The coating components are calculated by weight: Calcite: 35.0 parts, calcined fluorite: 28.5 parts, calcined natural rutile: 3.0 parts, quartz sand: 3.0 parts, sprayed ferrosilicon: 3.0 parts, nickel powder: 6.3 parts, soda ash: 0.7 parts, CMC: 0.6 parts, sodium alginate: 0.6 parts, low-carbon ferromanganese: 5.9 parts, atomized iron powder: 9.0 parts, ferrotitanium: 2.0 parts, rare earth oxide: 0.8 parts, rare earth fluoride: 1.0 parts, zirconium dioxide: 0.6 parts.

5. A welding rod for high head steel of a pumped storage power station according to claim 1, characterized in that: The coating components are calculated by weight: Calcite: 26.9 parts, calcined fluorite: 33.0 parts, calcined natural rutile: 4.0 parts, quartz sand: 4.0 parts, sprayed ferrosilicon: 2.5 parts, nickel powder: 5.5 parts, soda ash: 0.8 parts, CMC: 0.3 parts, sodium alginate: 1.0 parts, low-carbon ferromanganese: 5.0 parts, atomized iron powder: 11.0 parts, ferrotitanium: 2.6 parts, rare earth oxide: 1.6 parts, rare earth fluoride: 0.8 parts, zirconium dioxide: 1.0 parts.

6. A welding rod for high head steel of a pumped storage power station according to claim 1, characterized in that: The mass ratio of the coating to the welding core is 3:6.5-7.

5.

7. A method for producing a welding rod for high-head steel used in a pumped-storage power station according to any one of claims 1 to 6, characterized in that: The steps include: Step 1, mixing the components of the coating evenly according to the proportion, adding an adhesive to the mixture, and mixing evenly; Step 2: Add the mixture prepared in the above step 1 and the welding core into a battening machine, prepare a coating on the surface of the welding core, and then bake it at low temperature and high temperature to obtain the welding rod.

8. The method for producing a welding rod for high-head steel of a pumped storage power station according to claim 1, characterized in that: In the step 1, the weight ratio of the adhesive to the mixture is 0.2 to 0.23:

1.

9. The method for producing a welding rod for high-head steel of a pumped storage power station according to claim 1, characterized in that: In the step 2, the temperature of the low-temperature baking is 85°C to 110°C, and the temperature of the high-temperature baking is 380°C.

10. The method for producing a welding rod for high-head steel used in a pumped storage power station according to claim 7, characterized in that: The adhesive is potassium sodium water glass, and its modulus ratio is 1:0.9-1.1.

Citation Information

Cited By

  • A welding rod and welding method for 1000mpa high-strength steel used in large-scale hydropower projects

    CN122787649A